An Analysis of cyber threats in distributed energy power networks - Kamble, Vijaykumar; Navale , Vandana; Dange , Varsha; Chaudhari, Archana (International Journal of Basic and Applied Sciences, 2025)
The power demand has increased dramatically in recent years. Conventional power generation provides about 80% of the world's energy. Distribution networks are essential to the electrical grid system because they link consumers to the transmission system. Distribution networks require careful planning since they are vast and complex. Congestion in the distribution network quickly affects the network's voltage profile as power demand increases, leading to power outages and delayed power delivery. Since Active Distribution Networks (ADNs) are more vulnerable to cyberattacks due to their integration with cutting-edge communication and control technologies, detecting these attacks is a critical problem in modern power systems. The possible cyberattacks on power systems are covered in this paper. To identify the possible, cyberattack, an IEEE-15 bus system with Cyber-Physical Layering (CPL) is suggested. Cyberattack detection systems defend ADNs against assaults including data alteration, illegal access, and service denial by utilizing machine learning, anomaly detection, and real-time monitoring. Using machine learning techniques, such as DT, NNN, and SVM, cyberattack detection is also carried out on modified IEEE-15 bus systems and CPL-based IEEE-15 buses. Additionally, a comparative analysis of the methods for cyberattack detection is conducted.The paper discusses how advanced communication and control systems in active distribution networks (ADNs) face heightened cyber risks from both traditional threats like DoS and FDI attacks and emerging quantum computing-based attacks. It highlights vulnerabilities across CPL layers and recommends AI/ML anomaly detection, quantum-safe cryptography, and robust network designs for future resilience.
Keywords: Cyberattacks, Vulnerabilities, Microgrid, Distributed System, Denial-of-Service, Communication, Algorithm